2008
DOI: 10.1038/modpathol.2008.147
|View full text |Cite
|
Sign up to set email alerts
|

Loss of 13q is associated with genes involved in cell cycle and proliferation in dedifferentiated hepatocellular carcinoma

Abstract: Dedifferentiation of hepatocellular carcinoma implies aggressive clinical behavior and is associated with an increasing number of genomic alterations, eg deletion of 13q. Genes directly or indirectly deregulated due to these genomic alterations are mainly unknown. Therefore this study compares array comparative genomic hybridization and whole genome gene expression data of 23 well, moderately, or poorly dedifferentiated hepatocellular carcinoma, using unsupervised hierarchical clustering. Dedifferentiated carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 40 publications
3
24
0
Order By: Relevance
“…miRNAs serve a negative role primarily through the inhibition of its target genes; a previous study has demonstrated that miR-15a induces the apoptosis of laryngeal carcinoma cells by activating Bcl-2 (26). It has been confirmed that miRNA-15a is able to inhibit the proliferation of laryngeal cancer cells by directly inhibiting PI3K/Akt expression (27). In the present study, it was identified that curcumin significantly increased miR-15a expression in AMC-HN-8 cells.…”
Section: Discussionsupporting
confidence: 63%
“…miRNAs serve a negative role primarily through the inhibition of its target genes; a previous study has demonstrated that miR-15a induces the apoptosis of laryngeal carcinoma cells by activating Bcl-2 (26). It has been confirmed that miRNA-15a is able to inhibit the proliferation of laryngeal cancer cells by directly inhibiting PI3K/Akt expression (27). In the present study, it was identified that curcumin significantly increased miR-15a expression in AMC-HN-8 cells.…”
Section: Discussionsupporting
confidence: 63%
“…Published studies on HCC have shown that chromosome region 13q is one of the most frequently affected chromosome arms in a number of cancers including HCC [22,23]. A recently published study has reported that allelic losses on 13q can result in more aggressive tumor behavior, suggesting that this chromosomal region is likely to contain TSGs [24,25]. In this study, we provide direct evidence for the tumor-suppressing role of PCDH9, which is located on chromosome 13q21.32 and frequently deleted in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Losses of 13q have been reported in 27% of surgical specimens of HCC as a sign of dedifferentiation [12] . The loss is also seen in the context of increasing chromosomal instability [16,17] . Deletion of 13q has been reported in other solid tumors, but with a frequency of less than 5% [18] .…”
Section: Discussionmentioning
confidence: 99%